Simulation Study on Blood Glucose Control in Diabetics - Li, Chengwei; Hu, Ruiqiang (2007 1st International Conference on Bioinformatics and Biomedical Engineering, 2007)
In this paper, some theoretical analysis of the control of blood glucose levels in diabetic individuals is undertaken using a simple mathematical model of the dynamics of glucose and insulin interaction in the blood system developed by Bergman et al. One is an open-loop control, which is based on the mathematical model of insulin curve. The other is a closed-loop control, which is using a classic PID controller. The aim of the control performance was assessed in terms of its ability to track a setpoint (70 mg/dl)form initial state of hyperglycemia, as well as in response to a meal disturbance. The MATLAB simulation is performed to manifest the theoretical analysis. The development reported in this paper are expected to simplify the insulin delivery mechanism, thereby enhancing the quality of life of the patient.